O compliance nas empresas estatais e a otimização da efetivação de políticas públicas - Souza, Marcus Vinícius de Souza e (2018)
The recent divulgation of several cases of corruption involving public assets brings urgency on the expansions of the debates over this theme. The current context, which includes the arrest of several of the biggest business man of the country and the finding of the misuse of billions of Brazilian Reais, renew the legitimacy of the debate herein proposed. The above mentioned expansion of debates, in this paper, includes the analysis of public owned companies as instruments of implementation of public policies, both by the payment of profits to the Estate and by directly performing on different aspects of society. Therefore, this paper intends to show that corruption is a factor of reduction of the effectivity of public policies, which leads to the need of measures to prevent, identify and combat such practices. Given the business structure they adopt, the suggestion is to accomplish such goal by implementing compliance measures, which consist on principles and measures intending to prevent, identify and combat of misuses, both patrimonial and regarding the activities of the companies. Therefore, this paper defends that compliance on public owned companies is essential to maximize the effectivity of public policies. Therefore, using analysis of national and international bibliography and of corruption cases, this paper concludes that compliance programs on public owned companies optimizes the implementation of public policies.